1997
DOI: 10.1159/000190163
|View full text |Cite
|
Sign up to set email alerts
|

Histological Localization of Advanced Glycosylation End Products in the Progression of Diabetic Nephropathy

Abstract: We studied the immunohistochemical localization of advanced glycosylation end products (AGEs) in the progression of diabetic nephropathy. Fourteen NIDDM patients with diabetic nephropathy were evaluated: 2 patients with normoalbuminuria, 4 with microalbuminuria (MA) and 8 with overt proteinuria (OP). Three patients with minor glomerular abnormalities were used as nondiabetic controls. Immunoreactivity to a monoclonal anti-AGE antibody (6D12) was recognized on the internal elastic membranes of arterial walls in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Although several AGE structures have been reported, our group (1) and Reddy et al (2) independently demonstrated that N ε -(carboxymethyl)lysine (CML) is a major antigenic AGE structure. CML concentration, adjusted for age and duration of diabetes, is also increased in patients who have diabetes with complications, including nephropathy (3)(4)(5), retinopathy (6), and atherosclerosis (7)(8)(9). CML is also recognized by receptor for AGE (RAGE), and CML-RAGE interaction activates cell signaling pathways such as NF-B and enhances the expression of vascular cell adhesion molecule-1 in human umbilical vein endothelial cells (10).…”
mentioning
confidence: 99%
“…Although several AGE structures have been reported, our group (1) and Reddy et al (2) independently demonstrated that N ε -(carboxymethyl)lysine (CML) is a major antigenic AGE structure. CML concentration, adjusted for age and duration of diabetes, is also increased in patients who have diabetes with complications, including nephropathy (3)(4)(5), retinopathy (6), and atherosclerosis (7)(8)(9). CML is also recognized by receptor for AGE (RAGE), and CML-RAGE interaction activates cell signaling pathways such as NF-B and enhances the expression of vascular cell adhesion molecule-1 in human umbilical vein endothelial cells (10).…”
mentioning
confidence: 99%
“…Immunohistochemical observations in diabeticrat models have shown AGE accumulation in the glomerular extracellular matrix [19,20]. In human diabetic patients, the accumulation of AGE, in particular, CML, pentosidine and malondialdehyde in glomerular lesions, is related to disease severity and in the presence of an up-regulated receptor for AGE (RAGE) in podocytes [21,22]. The toxic effects of these AGE result from structural and functional alterations in plasma and extracellular matrix (ECM) proteins, in particular, from cross-linking of proteins and interaction of AGEs with their receptors and/or binding proteins.…”
mentioning
confidence: 99%
“…AGEs are known for their heterogeneity, including pyrraline, pentosidine, crossline, and carboxymethyllysine. Some reports have described excessive amounts of AGEs in renal tissue specimens from diabetic patients [2, 3, 4, 5]. Carboxymethyllysine, a major chemical component of AGEs that accumulates in tissue proteins [15], is found in the expanded mesangial matrix and in the thickened glomerular basement membrane [16]in diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…AGEs have been found to accumulate in the glomeruli of diabetic patients with nephropathy [2, 3, 4, 5]. Since AGE measurement in tissue specimens is not useful in clinical practice, analysis of blood samples has been pursued.…”
Section: Introductionmentioning
confidence: 99%